SHARIA FINTECH: CURRENT ISSUES AND FUTURE OPPORTUNITIES - Aulia, Dina; Syukron, Muhammad; Khomsiyah, Khomsiyah (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
This research was conducted to determine the present and future focus on topics related to sharia fintech through the bibliometric and visualization analysis of 380 papers retrieved from the Google Scholar database. The process was based on cluster analysis as well as the evaluation of events and all keywords. The results showed that publications related to sharia fintech increased rapidly since the beginning of 2016. Moreover, the most prolific journals, cities, regions, institutions, and authors identified were JIEI, Jakarta, West Java, STIE AAS, and T Trimulato respectively. The most frequent keywords were Sharia Fintech, Indonesia, Fintech, and Sharia. The six main research trends identified included Principles and Practices of Islamic Finance, Innovative Financial Technology, Studies or Research on Financial Technology, Fintech Association and MSME Development in Indonesia, Covid Analysis and Case Studies in the Context of Sharia Fintech, as well as Sharia Peer Lending. Therefore, this research was able to provide a comprehensive analysis of the trends in Islamic fintech and identify future directions.